Natural and synthetic layered hydroxide salts (LHS): Recent advances and application perspectives emphasizing catalysis. (December 2021) - Nakagaki, Shirley; Machado, Guilherme Sippel; Stival, João Felipe; Henrique dos Santos, Everton; Silva, Gabriel Machado; Wypych, Fernando
Abstract: Layered hydroxide salts (LHS) are synthetic and natural materials with the general chemical composition M 2+ (OH)2− x (A m − ) x / m (M 2+ is a divalent cation, normally Mg 2+, Ni 2+, Zn 2+, Ca 2+, Cd 2+, Co 2+ or Cu 2+, and (A m − ) x / m · n H2 O is a hydrated counter-ion). In most of the cases, the LHS structures are based on the modification of the layered magnesium hydroxide-like structure (brucite, Mg(OH)2 ), in which part of the structural hydroxide groups (OH − ) from the Mg 2+ centered octahedra sharing edges are replaced by water molecules or anions. This process creates a net positive charge in the layers, which needs to be compensated with the intercalation/grafting of hydrated anions. Despite LHS versatility and having great potential for academic and industrial applications due to the variable chemical compositions, structures, and properties, this material is less explored in the literature. In the present review, the structures of the majority of the LHS materials are described and their potential applications are discussed, emphasizing their usage as supports for metalloporphyrins and utilization in different catalytic reactions. Graphical abstract: Image 1 Highlights: Layered hydroxide salts (LHS), historical, definitions, uses and applications. LHS, materials with variable chemical compositions, structures and properties. LHS, synthetic and natural materials which can exchange anions and/or cations. LHS as support for metalloporphyrins and application in different catalytic reactions. LHS as potential materials for several academic and industrial applications.